PENGARUH OVERLOAD INFORMASI TERHADAP PEMROSESAN KOGNITIF SISWA DALAM PEMBELAJARAN DIGITAL - Yulfiliantoro, Sachsya Gyanvanovyandhis; M. Mamduh Winangun (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The development of digital learning in Indonesia has brought ease of access to information, but on the other hand, new problems have emerged in the form of information overload, which affects students' thinking abilities. This condition is related to the limited capacity of working memory within cognitive learning theory, which emphasizes that the process of understanding information requires structured processing. This article aims to examine how information overload impacts students' cognitive processing in digital learning. The method used is a literature study by reviewing various national scientific journals and books relevant to cognitivist theory and the stated topic. The analysis shows that excessive exposure to information can disrupt focus, reduce concept comprehension, and cause mental fatigue in students. This occurs because the information received excessively exceeds the inadequate capacity for processing in working memory, resulting in suboptimal storage of memory in long-term memory. Therefore, more structured learning strategies are needed, such as simplifying materials, using more proportional media, and managing cognitive load to make the learning process more effective and lighter for students.